A randomized control trial of a virtual reality learning environment in obstetric medical student teaching. (December 2022) - Kane, D.; Ryan, G.; Mangina, E.; McAuliffe, F.M.
Abstract: Background: Virtual reality learning environments (VRLE) have the potential to transform the delivery of teaching in obstetrics. Medical students often find it difficult to conceptualize fetal lie and presentation. Methodology: We conducted a single-centre randomized control trial of medical students using VRLE (n = 35) to depict fetal lie and presentation, compared with a control group (n = 34) using traditional 2-dimensional images. The VRLE, delivered using a mounted display headset, created an immersive experience exploring fetal lie and presentation. Clinical examination skills were then assessed using an obstetric abdominal model. The primary outcome was knowledge, as assessed by determination of fetal lie and presentation on an obstetric model. Secondary outcomes were time taken to successfully complete the task, and the student experience. Results: There was a non-significant trend towards improved knowledge outcomes using the VRLE compared to traditional methods with 70 % (n = 23) in the VRLE group determining the correct fetal lie and presentation compared with 56 % (n = 19) in the control group (OR.551 CI 0.202–1.504, p = 0.242). Students in the intervention group more efficiently completed the task (45 s ± 12.95 vs 38 s ± 10.83 CI 1.701, 13.367p = 0.012) and better enjoyed the virtual learning experience with student confidence and satisfaction scores significantly higher (p = 0.02). Conclusion: It is feasible to use VRLE to teach medical students clinical skills such as fetal lie and presentation, enhancing the learning experience in both student satisfaction and confidence, with positive trends towards improved knowledge outcomes demonstrated.